Perception of Pamong Teacher on Teaching Skills of PAI Educational Field Practices (PLK) in Padang City - Nuraisyah, Adira; Rahman, Rini (EDUMALSYS Journal of Research in Education Management, 2023)
The background of this research is that there are still various problems when students carry out Educational Field Practices (PLK), which are related to student teaching skills. The purpose of this study was to find out how the teacher's perception or view of the teaching skills of PLK students of the Islamic Religious Education Study Program, Padang State University who carried out PLK at Air Tawar Barat Padang High School, to be precise at Pertiwi 1 High School and Labor UNP High School. The method used in this study is a qualitative method with a case study approach. The object of research is 6 tutor teachers. Based on the results of the study, showed that the teaching skills of students according to the perception or view of the tutor showed that (1) the skills to open and close lessons in general were good, only that students forgot to put forward indicators and motivate students, (2) skills in explaining material were good, able to use media learning that attracts students, conveys indicators and learning objectives, but in mastering the material is less in-depth and needs enrichment. (3) class management skills are quite good, students are still confused and overwhelmed in dealing with student behavior.